The adventures of Sherlock Holmes - Doyle, Arthur Conan, Sir, 1859-1930. (New York : Tor, 1989)
A collection of Sherlock Holmes mystery adventures, including "A Scandal in Bohemia," "The Red-headed League," and "The Adventure of the Speckled Band.".
"A Tom Doherty Associates book.".
Young Adult
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Holmes, Sherlock (Fictional character) -- Fiction; Mystery fiction; Private investigators -- Fiction